Polymers Based on Stable Phenoxyl Radicals for the Use in Organic Radical Batteries. Issue 9 (20th March 2014) - Jähnert, Thomas; Häupler, Bernhard; Janoschka, Tobias; Hager, Martin D.; Schubert, Ulrich S.
<x xml:space="preserve">Abstract</x> Polymers with pendant phenoxyl radicals are synthesized and the electrochemical properties are investigated in detail. The monomers are polymerized using ring‐opening metathesis polymerization (ROMP) or free‐radical polymerization methods. The monomers and polymers, respectively, are oxidized to the radical either before or after the polymerization. These phenoxyl radicals containing polymers reveal a reversible redox behavior at a potential of −0.6 V (vs Ag/AgCl). Such materials can be used as anode‐active material in organic radical batteries (ORBs). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>